Optimized production and immunogenicity of an insect virus-based chikungunya virus candidate vaccine in cell culture and animal models. Issue 1 (1st January 2021) - Adam, Awadalkareem; Luo, Huanle; Osman, Samantha R.; Wang, Binbin; Roundy, Christopher M.; Auguste, Albert J.; Plante, Kenneth S.; Peng, Bi-Hung; Thangamani, Saravanan; Frolova, Elena I.; Frolov, Ilya; Weaver, Scott C.; et al.
ABSTRACT: A chimeric Eilat/ Chikungunya virus (EILV/CHIKV) was previously reported to replicate only in mosquito cells but capable of inducing robust adaptive immunity in animals. Here, we initially selected C7/10 cells to optimize the production of the chimeric virus. A two-step procedure produced highly purified virus stocks, which was shown to not cause hypersensitive reactions in a mouse sensitization study. We further optimized the dose and characterized the kinetics of EILV/CHIKV-induced immunity. A single dose of 10 8 PFU was sufficient for induction of high levels of CHIKV-specific IgM and IgG antibodies, memory B cell and CD8 + T cell responses. Compared to the live-attenuated CHIKV vaccine 181/25, EILV/CHIKV induced similar levels of CHIKV-specific memory B cells, but higher CD8 + T cell responses at day 28. It also induced stronger CD8 +, but lower CD4 + T cell responses than another live-attenuated CHIKV strain (CHIKV/IRES) at day 55 post-vaccination. Lastly, the purified EILV/CHIKV triggered antiviral cytokine responses and activation of antigen presenting cell (APC)s in vivo, but did not induce APCs alone upon in vitro exposure. Overall, our results demonstrate that the EILV/CHIKV vaccine candidate is safe, inexpensive to produce and a potent inducer of both innate and adaptive immunity in mice.